If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(7x + -5) + 3 = 5(3x + 2) + -4 Reorder the terms: 2(-5 + 7x) + 3 = 5(3x + 2) + -4 (-5 * 2 + 7x * 2) + 3 = 5(3x + 2) + -4 (-10 + 14x) + 3 = 5(3x + 2) + -4 Reorder the terms: -10 + 3 + 14x = 5(3x + 2) + -4 Combine like terms: -10 + 3 = -7 -7 + 14x = 5(3x + 2) + -4 Reorder the terms: -7 + 14x = 5(2 + 3x) + -4 -7 + 14x = (2 * 5 + 3x * 5) + -4 -7 + 14x = (10 + 15x) + -4 Reorder the terms: -7 + 14x = 10 + -4 + 15x Combine like terms: 10 + -4 = 6 -7 + 14x = 6 + 15x Solving -7 + 14x = 6 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. -7 + 14x + -15x = 6 + 15x + -15x Combine like terms: 14x + -15x = -1x -7 + -1x = 6 + 15x + -15x Combine like terms: 15x + -15x = 0 -7 + -1x = 6 + 0 -7 + -1x = 6 Add '7' to each side of the equation. -7 + 7 + -1x = 6 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = 6 + 7 -1x = 6 + 7 Combine like terms: 6 + 7 = 13 -1x = 13 Divide each side by '-1'. x = -13 Simplifying x = -13
| 8r-5=45-2r | | 15x(4+8)-33=153 | | 10x+4x+4+8=3x+3+10x | | 4+7z=20+-3z | | 7x+3x-5x= | | x+2(x+4)=39 | | 9-1=b | | (21b-7)-5(4b+4)=-5 | | 7x-(x+4)-(2x+1)=10 | | Y=3x+1+3 | | Y=3x+1+1 | | 7y+7/3=4 | | 5x+-10=9x+26 | | -10+7x+1=46 | | 75=3(-10t-3)+5t | | 5t=42-t | | 2a=20-2a | | 28x+12=21+19x | | (110-8x)=3x | | f(41f-43)=0 | | 3(3x+7)=18 | | -7(6+8n)=-14 | | n^2+n+12=0 | | 425+25x=275+30y | | 1/5z+z+9=-9 | | 9x=9x+12 | | x^2+3x-2=x | | X=14x+1500 | | ln(3)+ln(x)=8.94 | | f(x)=-6x-10 | | x(m+6)+y(m-7)=z(m-9) | | 2n^2+2n+18=0 |